PEPE' PEPE' BAINE DANCE DANCER RECRUITMENT SYSTEM AT SIRAJUDDIN SANGGAR GOWA REGENCY - Selfiana Saenal; M Jazuli; Syakir Syakir (Universitas Negeri Makassar, 2023)
Pepesaat dance performance is one of the dance performances that began to develop in modern society such as Makassar. In the quality of performance, the role of the organization becomes important to be able to continue to develop following the changing times and the needs of society. Sanggar Sirajuddin Gowa is famous for the Pepe-pepe'Baine dance which is often performed at various events as a means of entertainment. The purpose of this study was to analyze the recruitment process of Pepe' Baine dancers at Sanggar Sirajuddin Gowa. The research method used is qualitative with a descriptive case study approach with interview, observation, and questionnaire data collection techniques. The results of the analysis showed that the process of recruiting dancers by Sanggar Sirajuddin was not specific but went naturally which made the Sanggar Leadership assess the feasibility of becoming a Pepe-pepe dancer. This is one of the reasons the number of dancers is only 9 people to date.